2014
DOI: 10.1016/j.chom.2014.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Functional Analysis of Plasmodium Protein Phosphatases Reveals Key Regulators of Parasite Development and Differentiation

Abstract: SummaryReversible protein phosphorylation regulated by kinases and phosphatases controls many cellular processes. Although essential functions for the malaria parasite kinome have been reported, the roles of most protein phosphatases (PPs) during Plasmodium development are unknown. We report a functional analysis of the Plasmodium berghei protein phosphatome, which exhibits high conservation with the P. falciparum phosphatome and comprises 30 predicted PPs with differential and distinct expression patterns dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
171
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(201 citation statements)
references
References 53 publications
15
171
1
2
Order By: Relevance
“…However, mCherry expression was completely lost in the oocysts at day 4 post infection. These results showed that P28::mCherry protein was expressed normally in this engineered parasite and is consistent with those observed using anti-P28 antibody staining [2325]. …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, mCherry expression was completely lost in the oocysts at day 4 post infection. These results showed that P28::mCherry protein was expressed normally in this engineered parasite and is consistent with those observed using anti-P28 antibody staining [2325]. …”
Section: Resultssupporting
confidence: 91%
“…Plasmodium P28 protein is expressed abundantly in activated female gamete, zygote, ookinete, and young oocyst [23, 24]. Antibody-based immuno-detection of P28 protein expression was widely used in studies of parasite gametocyte activation and ookinete formation [25]. To tag the endogenous PyP28 gene with red fluorescence protein mCherry gene, we made two constructs based on the pYC and pYCm plasmids, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…with either 5 × 10 6 wildtype (WT) or Δ psop25 iRBCs. For each genotype, blood smears were used to monitor daily parasitemia, gametocytemia (mature gametocytes per 100 RBCs), and the gametocyte sex ratio (female: male ratio) [33]. To quantify male gamete exflagellation, 10 μl of P. berghei -infected blood collected from mouse tail vein on day 3 p.i.…”
Section: Methodsmentioning
confidence: 99%
“…Also, depletion of the metallo‐dependent protein phosphatase PPM1 in P . berghei results in impaired exflagellation (Guttery et al ., 2014), while depletion of the Ca 2+ ‐dependent phosphatase Calcineurin affects male gametogenesis and subsequent fertilization in the rodent malaria parasite (Philip and Waters, 2015) (Fig. 1).…”
Section: The Initiation Of Gametogenesismentioning
confidence: 99%
“…Further, deletion of the Shewanella‐like protein phosphatase (SHLP1), PPM2 or the kelch‐like domain‐containing phosphatase PPKL results in impaired P . berghei ookinete development, and phenotypes include impaired IMC and microneme formation (Guttery et al ., 2012b, 2014; Philip et al ., 2012; Patzewitz et al ., 2013) (Table 1). …”
Section: The Zygote‐to‐ookinete Conversionmentioning
confidence: 99%